PERAN BAHASA INDONESIA DALAM MEWUJUDKAN KOMUNIKASI INKLUSIF DI DUNIA PENDIDIKAN - Sari, Winda Purnama; Ayu Faizatul Mabrurah; Imas Masidah Zianatul Millah; Nonny Rulisty Putri Sutikno (Jurnal Lentera Edukasi, 2025)
The Indonesian language plays an important role in building fair and inclusive communication in the educational world. The diversity of social backgrounds, cultures, and abilities of learners demands a means of communication that can bridge these differences. This study aims to outline how Indonesian as a national language, contributes to creating an equal and inclusive learning environment. Using a conceptual approach of library study this article highlights the role of language in shaping harmonious interactions, as well as the importance of empathic and adaptive use of language by educators. The results of the study show that the inclusive application of Indonesian language can increase learning participation, decrease the potential for discrimination, and strengthen social cohesion in the educational environment.